Pengaruh Pandemi Covid-19 Terhadap Efektivitas Belajar Siswa Kelas VI SDN Cikampek Barat 4 Pada Saat Di Rumah - Ajeng Annisa; Amaliyah; Nuraeni (Program Studi PGSD Kampus UPI di Serang, 2020)
The Covid-19 pandemic had a major impact in almost all countries, including Indonesia. Especially in the world of education, Covid-19 was also affected. The government issued a policy that requires every school to stop teaching and learning activities directly to minimize the spread of the dangerous Covid-19. This research was motivated by the researchers' curiosity about the effect of the Covid-19 pandemic on the effectiveness of student learning. The difference in learning methods that usually take place in class and face-to-face by the teacher, during the Covid-19 pandemic, teaching and learning was changed to online learning. Where teachers and students cannot study offline as usual in the classroom. The method used is interviews to find out the opinions of students, parents, and teachers. The results of interviews with students, namely students better understand learning when at school because the material at school will be delivered by the teacher. The results of interviews with the parents of students, namely when the students were at home, the parents could not always accompany them, because the parents had jobs that could not be left behind. The results of the teacher interview, namely the teacher explained that not all students have electronic devices that support learning, then the teacher applies thestrategy home visit (direct visits to students) or group study which is held once a week by paying attention to and implementing applicable health regulations